Coronal Resorption in Unerupted Anterior Permanent Teeth: Cases with Different Aetiologies? A Review. (2nd April 2022) - Makwana, Meeral; Murray, Alison
Abstract : Two case reports are described along with differential diagnoses and management strategies from the literature for teeth discovered with intra-coronal resorption prior to their eruption. Our cases feature impacted maxillary anterior teeth. In both instances, significant coronal resorption presented itself mid-way through fixed appliance treatment, prior to full eruption of the involved teeth. This was detected radiographically and not through patient-reported symptoms. Once sufficiently erupted, root canal therapy was carried out in both cases and orthodontic treatment was successfully completed. CPD/Clinical Relevance: Orthodontists are often first to identify pathological lesions in unerupted teeth and should be equipped with differential diagnoses in order to manage and refer patients appropriately.